PENDAMPINGAN LITERASI KEUANGAN UMKM KERANG INDAH BERBASIS ANDROID KECAMATAN SOREANG KOTA PAREPARE - Tarawiru, Yasri; Rahmawati, Rahmawati; Suwardoyo, Untung (Arunika: Jurnal Pengabdian Masyarakat, 2024)
MSMEs are now getting attention from the government and the general public now, because MSMEs can improve the community's economy, such as MSMEs of Kerang Indah Craftsmen in Soreang District which are able to produce various handicraft products from sea shells, but so far there are still many MSMEs that have not been able to make financial reports. able to distinguish or classify production costs such as the cost of Raw Materials, Labor Costs, and Factory Overhead Costs to make financial reports with MSME standards. The method used is Community Service, the first is observation, the second is socialization of MSME financial reports, the third is assistance in preparing financial reports, the fourth is training in preparing financial reports, evaluating whether MSME Shellfish Craftsmen are able to generate profits or losses as a shellfish craftsman business. the. The benefit of this community service is that it will gradually provide knowledge and skills in classifying production costs such as the cost of Raw Materials, Labor Costs, and Overhead Costs to make financial reports with MSME standards.